Multicarrier PWM techniques for three phase modular multilevel converter application in MRI systems - Devendiren, Shobana; Babu, Samuel Rajesh (Institute of Advanced Engineering and Science, 2024)
This research paper presents about the performance analysis of three phase modular multilevel converter with level shifted (phase disposition pulse width modulation) and phase shifted pulse width modulation (PWM) method. This research not only discusses the significance of different modulation procedures in the context of modular multilevel converters but also carefully evaluates each of their unique performance characteristics. This research is based on the fundamental creation of pulses and patterns that can only be acquired by comparing sinusoidal reference signals with triangular carrier signal. Both levels shifted (phase disposition) and phase shifted PWM procedures are used to calculate the phase output voltage of a converter at 2N+1 level. The output waveform is crucially shaped by these modulation techniques, which also ensure effective energy conversion and lower harmonic content. On the basis of the output voltage waveform's quality, the comparative research is conducted and simulated results were presented.